Nigeria: The Effects of Identity Politics on Societal Security - Aydın, Hakan (My University, 2023)
Nigeria is prominent country of the African continent with its population, economy and energy resources. Political problems have shaped the security agenda of Nigeria, which was exposed to British colonialism, since the independence declared in 1960. The interruption of democratic processes with the emergence of military coups after the civil war environment and the declared republics between the years 1960-1999 is an indication that a societal security environment could not be established. The reason for this is the failure to ensure the integration of segments with different ethnic and religious characteristics. With the concept of identity being placed at the center of political discussions, terrorist activities of organizations with fundamentalist ideas are encountered. There is the Boko Haram terrorist organization in Nigeria, which has settled in an international context in connection with other organizations that have had an impact on the regional framework in the last 10 years. In this article, the terror problem of Nigeria is examined through historical, political, economic and societal dynamics. Although the identity politics approach that is constructed and formed is thought to be the main factor in the problem of terrorism, the importance of societal and economic development in overcoming this issue is emphasized when the interregional differences in Nigeria are taken into account.
Keywords: Nigeria; identity; societal security; British colonialism; Boko Haram.